THE ENERGY BALANCE AND SUSTAINABILITY OF DYNAMIC SYSTEMS - A. A. Kolesnikov; P. A. Koropets; A. V. Kukharskiy (Современная наука и инновации)
The article presents a method for creating a system with specified stability properties. The system parameters are obtained under the conditions of the energy balance between the power supplied and dissipated in the process of self-oscillations. The effect of stabilization of initially unstable system due to the installation of dynamic self-oscillation dampener is considered. The example of calculation of parameters of dynamic dampener of self-oscillations is given. The method for assessing the sustainability of the system required the orthogonality property of own forms of fluctuations. The characteristic difference of the proposed method from other known stability criteria is that the energy balance conditions are recorded directly in the parameters of the dynamic system itself.